Study of Spatial Distribution and Characteristics of Littering Spots in Houy-Markhiew Watershed, Vientiane Capital - Pengsisomboun, Souvanna; Paphaphanh, Phetphoumin; Kunyalong, Lodtharluk; Phongthady, Nansy; Chansompou, Vathanamixay; Phonpaserd, Phongphaiboun (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The situation of littering spot is the common problem and many places in Vientiane Capital has littering spot in many area. The aims of this study are: 1). to study the spatial distribution and characteristics of people’s littering, 2). To study the amount and type of waste founded. GPS Survey and visual interpretation was investigated for spatial distribution and characteristics of each littering. The amount of waste ware estimated width, length and height of the garbage in term of volume. However, waste types ordered in to 3 ranks, 1 order of garbage is found per point to calculate the percentage of the type of garbage found for each type of garbage. The result of the study ware found that a total of 155 points of reckless dumping scattered along roads, along streams, and vacant land between villages. The condition of most of the garbage is household waste that has not been sorted and some places have scar of the burning. The volume of spam found all 885.868 cubic meters, width average 2.42 meters, length average 5.14 meters, height average 0.27 meters and average volume 5.71 cubic meters. The waste type ware found Grocery bags, Other, beverage bottle, Other plastic bags and sheet, food wrapper and sachet (candy, chips, tobacco, ketchup), cup and plate, diaper, take out/away container, rope, other plastic bottles (shampoos, detergents, oil, bleach, etc.), cutleries (straws, stirrers, forks, knives, spoons, chopsticks), Textile/Clothes and Fishing gear 29.25%, of the 18.24%, bottle drinks found 11.83%, bags, sheet plastic and other 9.68%, wrapping food (candy, tobacco) 8.60%, glass plates and cups 8.39%, diapers 7.09%, food boxes 4.52%, other plastic bottles (boxes, hair, coffee bags, oil, etc.) 0.65%, cutting tools (forks, knives, spoons) 0.64%, textiles clothing 0.22%, respectively, and no litter to dispose of litter or trash can, no trash to cause.